Beyond tobacco – the secondary impact of substance misuse in chronic obstructive lung disease. (1st February 2022) - Macmurdo, M.; Lopez, R.; Udeh, B. L.; Zein, J.
Abstract: Background Chronic obstructive lung disease, specifically chronic asthma and COPD, impacts more than 500 million adults worldwide, and is associated with high healthcare spending and significant disease-related morbidity. While the direct impact of substance use disorder is well documented, little is known about the indirect impact of substance misuse within this patient population. The healthcare cost and indirect morbidity secondary to substance misuse in obstructive lung disease has yet to be quantified. Objective To determine the indirect impact of substance misuse on disease severity, healthcare utilization and healthcare costs in patients with chronic obstructive lung disease across the United States. Methods Utilizing data from the 2012–2015 National Readmissions Database (NRD) patients with a diagnosis of COPD or asthma were identified. Documented substance misuse, rates of hospitalization, frequency of hospital readmission, markers of admission severity and cost were assessed utilizing weighted regression analysis. Results A total of 1, 087, 226 patients with an index admission for asthma or COPD were identified. Substance misuse was documented in 4.0% of patients. Substance misuse was associated with a 30% increase in odds of readmission and a higher cost per index admission. The additional index admission costs totaled $24 million for our cohort. Conclusion Substance misuse is associated with an increase in healthcare utilization and healthcare cost in patients with chronic obstructive lung disease. Targeting substance misuse in this patient population has the potential for significant cost savings to the healthcare system.